O heterocontrole da fluoretação da água de abastecimento público na percepção dos trabalhadores da vigilância no Estado do Espírito Santo - Porto, Ana Carla Layber (2025)
Water fluoridation for human consumption is the most relevant public health measure due to its proven effectiveness in controlling dental caries. The environmental health surveillance sector in municipalities is responsible for the external monitoring (heterocontrol) of water fluoridation, ensuring optimal fluoride levels in the water supply, promoting oral health among the population, and minimizing associated risks. Several failures in the heterocontrol process have been reported. This study aimed to assess the perceptions of environmental health surveillance workers regarding the heterocontrol of public water supply fluoridation in the state of Espírito Santo, Brazil. A qualitative approach was adopted, involving ten environmental health surveillance professionals from nine municipalities of varying population sizes across the three health regions of Espírito Santo (Brazil). Individual interviews were conducted using a semi-structured script, recorded, and fully transcribed. Thematic Content Analysis was performed following Bardin's methodology. Heterocontrol of water fluoridation was recognized as important for water quality, although it was not carried out by eight of the interviewees. Training and state-level support were identified as facilitators of water quality surveillance, whereas lack of supplies and transportation, work overload, staff turnover, and insufficient training on fluoridation and its monitoring were reported as barriers. Positive perceptions of water surveillance work predominated, highlighting its social relevance. Negative perceptions stemmed primarily from excessive workloads and lack of training, the latter being the most frequently cited area for improvement within the Vigiagua Program. It is concluded that heterocontrol of fluoridation was only marginally associated with water quality, and that effective surveillance work depends on the provision of adequate working conditions for monitoring fluoride levels, ensured by health managers, including permanent education programs. In this way, water surveillance will become more effective, integrating fluoridation as an essential component of water quality.